Epiphreatic caves in Niah karst tower (NW Borneo): Occurrence, morphology and hydrogeochemistry - Dodge-Wan, D.; Prasanna, Mohan Viswanathan; Ramasamy, Nagarajan; Anandkumar, A. (Zalozba Z R C, 2017)
© 2017, Zalozba Z R C. All rights reserved. Epiphreatic caves develop close to the water table at the boundary between vadose and phreatic karst zones. The recognition of their former existence and position in uplifted limestone regions can inform on phases of uplift, base level lowering and rate of vertical deepening of the karst. Hence, epiphreatic caves and the karst processes that form them are of specific interest. Although the large and spectacular caves of Niah have been subject of much research and interest, the existence of small epiphreatic caves at the foot of the karst towers has not previously been documented in this region of NW Borneo. The study documents and reports an epiphreatic cave passage at water table elevation in the Painted Cave karst tower where several large caves are also known. The semi-flooded passage is over 480 m long and traverses the tower from east to west, intersecting other much larger vadose caves. The epiphreatic flow path is characterized by a number of sinking streams and resurgences as well as several sharp bends in the passage indicating joint control. As an initial attempt this study was undertaken to correlate the water chemistry along the cave path to understand the geomorphological controls. A preliminary campaign of water sampling was carried out with samples collected at ten locations along the path of the cave stream and analyzed for pH, EC, TDS, DO, Eh, major ions, nutrients and trace metals. The results show that dissolution of host rock and leaching of organic matter are the dominant controlling factors for the geochemistry of surface water along the cave stream passage. During dry conditions the water was under-saturated for carbonate minerals but not aggressive suggesting that most dissolution and erosion occurs during flood conditions. This is supported by the morphology of the passages and features of the rock wall both inside the caves and at the foot of the karst tower.